Gesundheitsseelsorge als gesundheitssensible Seelsorge - Noth, Isabelle (Wege zum Menschen, 2025)
The article deals with the topic of "health-sensitive pastoral care" and calls for an expansion of the perspective, away from a fixation on institutions towards a subject-centered and community-oriented pastoral care that actively shapes the socio-political discourse. It emphasizes how important it is not only to define health in medical terms, but also to adopt a theological perspective.